How Youtube Beauty Vlogger Review, Self Congruity and Price Perception Influence Impulse Buying and the Impact On Repurchase Intention (Case Study at Teenager Users of Emina Cosmetics In Surabaya) - Dewi Apriliani; I Gede Arimbawa; Ani Wulandari (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aims to analyze the influence and significance of YouTube beauty vlogger review, self congruity and price perception to impulse buying as well as their impact on the repurchase intention of young girls using Emina cosmetics in Surabaya. This research was using a quantitative method. The research data are primary data obtained from a sample of 100 young girls of Emina cosmetics users in Surabaya as the respondents. Data collected from online questionnaires and then analyzed using Partial Least Square (PLS) which processed by SmartPLS 3 version 3.6.8 software. The result of this research indicated that YouTube beauty vlogger review did not have a significant impact on impulse buying and repurchase intention. While the self-congruity and price perception significantly affected impulse buying and repurchase intention. Therefore, Emina should be focusing to strengthen its brand identity and maintain the affordability of their product rather than collaborating with beauty vlogger as their promotion strategy.